Pengetahuan Dan Tindakan Penderita Tb Paru Tentang Teknik Dan Tujuan Batuk Efektif Untuk Bersihan Jalan Nafas - Batubara, Khairunnisa (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Effective coughing is a method of coughing correctly, where the client can save energy so that he does not get tired easily and can expel phlegm optimally. Effective coughing technique is an action taken to clear secretions from the respiratory tract. The aim of an effective coughing technique is to expel phlegm attached to the throat, dilute phlegm, reduce shortness of breath due to phlegm accumulation, increase oxygen levels in the body, facilitate clearing of the respiratory tract, avoid splashes of phlegm. This research uses a